"Fix My Life": Oprah, post-racial economic dispossession, and the Precious transfiguration of PUSH. (March 2014) - Williams, Kim D Hester
This article examines the critical interventions of Black feminist discourses that advocate for oppositional knowledges and a womanist ethics of care and communalism versus the media-driven hypervisible representation of Black racial subjects that promote neoliberal individualism. The article devotes particular attention to how the 1996 novel, PUSH, by Sapphire, foregrounds the racially oppressive neoliberal welfare reform policies of the 1980s and 1990s while Oprah Winfrey's coproduction of the 2009 film adaptation of the novel, retitled Precious, functions in opposition to Sapphire's feminist narrative. The article highlights the Oprah brand's emphasis on neoliberal self-sufficiency and personal responsibility despite ongoing racial and economic dispossession and discusses, in relation, the promotion of Iyanla Vanzant's Oprah Winfrey Network television program, Fix My Life, as further reinforcing the post-racial, neoliberal antiwelfare state.